Synthesis and Biological Evaluation of Herceptin-Conjugated Liposomes Loaded with Lipocalin-2 siRNA for the Treatment of Inflammatory Breast Cancer - Marienid Flores-Colón; Mariela Rivera-Serrano; Esther A. Peterson-Peguero; Pablo E. Vivas-Rivera; Fatima Valiyeva; Pablo E. Vivas-Mejía (Pharmaceuticals)
Background: Inflammatory breast cancer (IBC) is a rare and aggressive subtype of breast cancer that accounts for 1–5% of BC patients and regularly affects women under 40 years of age. Approximately 50% of IBC cases are HER2+ and can be treated with the monoclonal antibody-based therapy Herceptin (trastuzumab). However, resistance to Herceptin develops within a year, and effective second-line targeted therapies are currently unavailable for IBC patients. Lipocalin-2 (LCN2) is a promising therapeutic target for IBC due to its role in promoting tumor invasiveness, angiogenesis, and the inflammatory tumor microenvironment characteristic of IBC. Objective: We developed Herceptin-conjugated liposomes loaded with LCN2-targeted small-interference RNA (siRNA) for HER2+ IBCs. Methods: We synthesized DSPE-PEG(2000)-maleimide-Herceptin in a three-step process and formulated the liposomes together with DOPC, PEG(2000)-PE, cholesterol, and siRNA. Results: Dynamic light scattering confirmed the liposome size distribution, which was 66.7 nm for the Herceptin-conjugated liposome versus 43.0 nm in a non-functionalized liposome. Here, we report efficient internalization of this formulation into HER2+ IBC cells, reducing LCN2 levels by 30% and disrupting tumor emboli formation. RNA sequencing revealed 139 genes that were differentially expressed upon LCN2 knockdown, with 25 canonical pathways identified through Ingenuity Pathway Analysis. Conclusions: These findings suggest that LCN2-targeted siRNA within Herceptin-targeted liposomes represents a promising therapeutic strategy for IBC.